Analisis pengaruh ukuran perusahaan dan fee audit terhadap kualitas audit - Annisa, Mutiara Lusiana; Amalia, Rizki Fitri (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2024)
This research aims to analyze the influence of company size and audit fees on audit quality in companies listed on the Jakarta Islamic Index (JII). The study utilizes secondary data obtained from official sources, including the Stockbit website (www.stockbit.com) and the Indonesia Stock Exchange (BEI) website (www.idx.co.id). Additional references from relevant journals are also used to support the research. The population of this study includes all companies listed on the Jakarta Islamic Index during the 2020–2023 period. The research sample is selected using a purposive sampling technique, comprising 8 companies observed over 4 years (2020–2023), resulting in 32 data points. The data analysis is conducted using logistic regression with the assistance of the SPSS program. Logistic regression is a statistical technique used to model the relationship between one or more independent variables (predictors) and a categorical dependent variable. The test results reveal the following findings (1) Company size has a partially negative effect on audit quality. (2) Audit fees have a partially positive effect on audit quality. This research provides insights into how company characteristics and audit-related factors influence audit quality in the context of Islamic-indexed companies in Indonesia.